Avaliação da limitação ventilatória e dos índices da potência circulatória e ventilatória de pacientes com doença arterial coronariana - Simões, Viviane Castello (2015)
This thesis consisted of two studies described below. The Study 1 aimed to investigate if expiratory flow limitation (EFL) present at moderate intensity exercise in subjects following myocardial infarction (MI) (as shown in a previous study conducted in our laboratory) already manifests in those with stable coronary artery disease (CAD). Forty-one men aged 40-65 years were allocated into four different groups: 1) stable coronary artery disease (SCADG) (n=9), 2) recent myocardial infarction (RMIG) (n=8), 3) late myocardial infarction group (LMIG) (n=12), and 4) health control group (CG) (n=12). Two cardiopulmonary exercise testing (CPX) at constant workload (moderate and high intensity) were applied and EFL was evaluated by exercise flow-volume loops. We observed that during moderate intensity exercise the RMIG and LMIG presented with a significantly higher number of subjects with EFL compared to the CG, while no significant difference was observed among groups at high intensity exercise. Regarding the degree of expiratory flow limitation, the RMIG and LMIG showed significantly higher values at moderate intensity exercise when compared to the CG. At high intensity exercise, significantly higher values for the degree of expiratory flow limitation were observed only in the LMIG compared to the CG. We concluded that an EFL was only present in MI groups (recent and late) during moderate intensity exercise; whereas at high intensity exercise all groups presented EFL. Thus, EFL observed at moderate intensity exercise in both MI groups may be linked to the consequences of event and not to CAD. Following, the Study II aimed to investigate the indexes of circulatory (CP) and ventilatory power (VP) in CAD patients. Eighty-seven men were studied aged 40-65 years, being 42 subjects in the CAD group and 45 in the CG. CPX was performed on a treadmill and the following measures were obtained: 1) peak oxygen consumption (VO2), 2) peak heart rate (HR), 3) peak blood pressure (BP), 4) peak rate-pressure product (peak systolic BP x peak HR), 5) peak oxygen pulse = (peak VO2/peak HR), 6) the oxygen uptake efficiency (OUES), 7) the carbon dioxide production efficiency (VE/VCO2 slope), 8) CP (peak VO2 x peak systolic BP) and 9) VP (peak systolic BP/VE/VCO2 slope). The CAD group had significantly lower values for peak VO2, peak HR, peak systolic BP, peak rate-pressure product, peak oxygen pulse, the OUES, CP and VP and significantly higher values for peak diastolic BP and the VE/VCO2 slope compared to the CG. Furthermore, a stepwise regression analysis showed that CP was influenced by the group and VP was influenced both by group and by number of vessels with stenosis after treatment. Given the findings, we concluded that the indices of CP and VP were lower in men with CAD compared to CG. Thus, both studies brought important findings related to the responses of the cardiovascular, pulmonary and musculoskeletal systems of patients with CAD during physical exercise, bringing many contributions to clinical practice and assisting in the prescription of exercise training.